2015
DOI: 10.1039/c5cc00968e
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide nanocapsules within silanized hydrogels suitable for electrochemical pseudocapacitors

Abstract: Soft biocompatible gels comprised of rolled up graphene oxide nanocapsules within the pores of silanized hydrogels may be used as electrochemical pseudocapacitors with physiological glucose or KOH as a reducing agent, affording a material suitable for devices requiring pulses with characteristic time less than a second.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This work builds on previous work where we have shown that Graphene Oxide (GO) incorporated in salinized PVA gels form rolled up graphene oxide nano capsules within the pores of salinized hydrogels may be used as electrochemical pseudo capacitors with physiological glucose or KOH as a reducing agent, affording a material suitable for devices requiring pulses with characteristic time less than a second [10].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This work builds on previous work where we have shown that Graphene Oxide (GO) incorporated in salinized PVA gels form rolled up graphene oxide nano capsules within the pores of salinized hydrogels may be used as electrochemical pseudo capacitors with physiological glucose or KOH as a reducing agent, affording a material suitable for devices requiring pulses with characteristic time less than a second [10].…”
Section: Introductionmentioning
confidence: 81%
“…Layer 2: this layer was prepared by first dispersing 100 mg dried GO and 200 micro liter's IL-EMImBrin 15 ml of distilled H2O and then sonicating it for 4 hours. This dispersion was slowly added to a PVA solution prepared by dissolving 3.25 g of PVA in 85 ml distilled H2O at 900C and allowed to cool to 500C, [10] The two layers were sandwiched together with a gel electrolyte. The gel electrolyte was made by adding 2 g of glucose or sodium citrate dehydrate and 75 ml of ILEMImBr to a solution of PVA cooled to 50 0C (Figure 1).…”
Section: Methodsmentioning
confidence: 99%